Theoretical approaches to improving the terminological apparatus of psychodiagnostic research in the system of the Ministry of Internal Affairs of Ukraine - V. I. Barko; V. V. Barko; O. O. Yevdokimova (Bulletin of Kharkiv National University of Internal Affairs)
The article provides a comprehensive analysis of the basic concepts and terms used in the field of psychological diagnostics. The scientific approaches to the formation of terms and conceptual apparatus by which this branch of psychological science describes its subject of study are considered. It is emphasised that the development of science is determined primarily by the formation of terminology, that is, its language as a system of general and specific concepts that are reflected in certain terms and signs. It is stated that the language of psychodiagnostics is a complex, multilevel, integral system, the elements of which are categories, concepts, terms, symbols. It is shown that in the course of the development of psychology, the conceptual apparatus is continuously being improved, definitions are being clarified, and the terminological vocabulary is being enriched. The current state of development of psychodiagnostics, the formation of promising theories of assessment and measurement of individual characteristics have necessitated the clarification of its terminological apparatus, a significant number of concepts, definitions, which are often contradictory, through the use of various approaches and terminological elements. It is emphasised that the conceptual and terminological apparatus of psychodiagnostics should be developed on the basis of modern realities, abandoning outdated approaches to the definition of certain concepts, and that work towards clarifying and unifying terms requires special care and validity.